Glaciers Control the Hydrogeochemistry of Proglacial Streams During Late Summer in the Wind River Range, Wyoming, United States - Barkdull, Natalie S.; Carling, Gregory T.; Fernandez, Diego P.; Nelson, Stephen T.; Bickmore, Barry R.; Tingey, David G.; Checketts, Hannah N.; Packer, Brian N.; Hale, Colin A. (Frontiers in Earth Science, 2021)
Glaciers alter the geochemistry of sensitive alpine streams by exposing freshly weathered bedrock and releasing atmospherically deposited trace metals from melting ice. Changes in the timing and quantity of glacial melt also affect discharge and temperature of alpine streams. To investigate the effects of glacier meltwater on the geochemistry and hydrology of proglacial streams in the western US, we sampled supraglacial meltwaters and proglacial streams in the Dinwoody Creek watershed in the Wind River Range, Wyoming during a one-week period in 2015. The upper watershed contains Gannett Glacier (~5 km2) and Dinwoody Glacier (~4 km2) at elevations between 3300–4000 m asl. Samples were collected during late summer (27 August – 4 September) when the contributions of glacier meltwater were highest. Supraglacial meltwater was enriched in a suite of trace metals (Cd, Co, Cu, Hg, Mn, Pb, Zn) relative to proglacial streams, suggesting an atmospheric source of metals to the glaciers. Concentrations of major ions and the remaining 30+ analyzed trace elements were enriched in proglacial streams relative to supraglacial meltwater, reflecting weathering of granite and gneiss bedrock. To evaluate the diurnal effects of glacier meltwater inputs, we deployed loggers to monitor water levels, temperature, and specific conductance at 15-min intervals over a one-week period and collected hourly water samples from Dinwoody Creek for a 24-hr period. The influx of glacial meltwater during the daytime diluted major ion and rare earth element concentrations and caused increased concentrations for a subset of trace metals. Stable water isotopes (δD and δ18O) in Dinwoody Creek were more depleted during peak flow relative to baseflow due to contributions from isotopically depleted meltwater. The combination of multiple hydrologic tracers (solute concentrations, high frequency logger data, water isotopes) shows strong potential to improve estimates of glacier meltwater contributions to proglacial streams. Changes in water chemistry and discharge need to be monitored as glaciers recede across the Wind River Range and other midlatitude mountain ranges for mitigating negative impacts on alpine ecosystems and downstream water resources.